2013
DOI: 10.1002/art.37861
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hyaluronan Synthesis Alleviates Inflammatory Responses in Murine Arthritis and in Human Rheumatoid Synovial Fibroblasts

Abstract: Objective. To clarify the roles of hyaluronan (HA) in joint inflammation and the process of joint destruction, using 4-methylumbelliferone (4-MU), an inhibitor of HA synthesis, in a mouse model of collagen-induced arthritis (CIA) and in a monolayer culture of fibroblastlike synoviocytes (FLS) derived from patients with rheumatoid arthritis.Methods. DAB/1J mice were immunized with type II collagen. The effects of 4-MU were evaluated by the physiologic arthritis score, paw swelling, the histologic arthritis scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 36 publications
4
61
0
2
Order By: Relevance
“…4-MU is known to inhibit HA synthesis by depletion of UDP-glucuronic acid and downregulation of HAS activity (Kakizaki et al 2004, Kultti et al 2009). At doses used in the present study, 4-MU alleviates inflammatory responses caused by excess HA synthesis in the collagen-induced arthritis mouse model in vivo and in vitro (Yoshioka et al 2013). We also observed that the glutamine analog DON, which inhibits glucosamine and consequent HA synthesis (Tempel et al 2000), acted on ovaries in the same manner as in vivo 4-MU.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…4-MU is known to inhibit HA synthesis by depletion of UDP-glucuronic acid and downregulation of HAS activity (Kakizaki et al 2004, Kultti et al 2009). At doses used in the present study, 4-MU alleviates inflammatory responses caused by excess HA synthesis in the collagen-induced arthritis mouse model in vivo and in vitro (Yoshioka et al 2013). We also observed that the glutamine analog DON, which inhibits glucosamine and consequent HA synthesis (Tempel et al 2000), acted on ovaries in the same manner as in vivo 4-MU.…”
Section: Discussionsupporting
confidence: 72%
“…Even when eCG was administered in combination with 4-MU or DON, HA production, normal follicle growth, and follicular avoidance of atresia were not observed. These two chemicals have been well known to reduce HA synthesis and have been frequently used for HA reduction studies in various cell lines and organs including ovary (Clark et al 1987, Tempel et al 2000, Kakizaki et al 2004, Kultti et al 2009, Tzuman et al 2010, Yoshioka et al 2013. On the other hand, these chemicals do not specifically exert effects on HASs, and therefore the relationship between follicular HA reduction and follicular atresia is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Vivo-We used 4MU, a well established and specific inhibitor of hyaluronan production (3,7,(13)(14)(15)(16)(17)20), to modulate hyaluronan synthesis. First, we confirmed the inhibitory influence of 4MU on hyaluronan synthesis by in vitro experiments.…”
Section: Mu Feeding Inhibits Hyaluronan Production In Vitro and Inmentioning
confidence: 99%
“…In the present study, we assessed the effect of hyaluronan in EAE by inhibiting hyaluronan synthesis with 4-methylumbelliferone (4MU) administration (3,(13)(14)(15)(16)(17). 4MU inhibits hyaluronan synthesis in a dose-dependent manner by two mechanisms: depletion of cellular UDP-glucuronic acid and down-regulation of hyaluronan synthases 2 and 3 (14).…”
mentioning
confidence: 99%
“…Additionally, 4-MU effects a pronounced reduction of HA synthase 2 (HAS2) transcription but by mechanisms that are currently unknown (32)(33)(34). As a potent inhibitor of HA, 4-MU has been used to examine the role of HA in epithelial-mesenchymal transitions (35), collagen-induced arthritis (36), invasion and metastasis of osteosarcoma (37) and breast cancer cells (38), inflammation and autoimmunity (31), chondrogenic differentiation (39), myofibroblast differentiation (40,41), and keratinocyte activation (42). We have shown that 4-MU blocks the assembly of pericellular coats on bovine, rat, and mouse chondrocytes and diminishes the responsiveness of chondrocytes to bone morphogenetic protein-7 similar to results obtained by hyaluronidase treatment (43).…”
mentioning
confidence: 99%